Butterfly Diversity of Kawal Tiger Reserve, Telangana, India - Jaiswal, Deepa; Bharath, B.; Karuthapandi, M.; Jadhav, Shrikant (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The present study accessed the butterfly diversity of Kawal Tiger Reserve, Telangana between March 2018 to February 2021. It shows the occurrence of 95 species belonging to the families Nymphalidae and Lycaenidae 29 species each, Pieridae 18 species, Hesperiidae 12 species, and Papilionidae 7 species. Within these, 9 species belong to Schedule I &II of the Indian Wildlife Protection Act 2022. The sampling has been carried out around 18 stations of the tiger reserve, in which Pulgampandri has 30 species and Rotiguda 25 species comparatively higher than that of other sampling stations. Prosotas noreia was rarely sighted and was first time recorded from the state of Telangana. Our goal is to explore and document butterfly fauna, which will serve as a valuable platform for butterfly conservation and quantitative diversity research.